2016
DOI: 10.1038/srep33071
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke is Associated with Hearing Threshold Shifts in Obese Adults

Abstract: Hearing loss resulted from multiple intrinsic and extrinsic factors. Secondhand smoke (SHS) and obesity had been reported to be related to hearing loss. This study explored the possible associations of SHS and obesity with the hearing threshold. The relations between SHS and the hearing threshold in subjects from three different body mass index classes were analyzed. Our study included data from 1,961 subjects aged 20–69 years that were obtained from the National Health and Nutrition Examination Survey for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Our results support the evidence that smoking and drinking have associations with the risk of hearing loss 26 27. Cruickshanks et al 28 estimated that current smokers were 1.69 times more likely to have hearing loss than non-smokers (95% CI 1.31 to 2.17), which is similar to the results obtained in our study (1.66-fold, 95% CI 1.24 to 2.22).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results support the evidence that smoking and drinking have associations with the risk of hearing loss 26 27. Cruickshanks et al 28 estimated that current smokers were 1.69 times more likely to have hearing loss than non-smokers (95% CI 1.31 to 2.17), which is similar to the results obtained in our study (1.66-fold, 95% CI 1.24 to 2.22).…”
Section: Discussionsupporting
confidence: 92%
“…Harmful habits, such as smoking and drinking, and ambient noise (including occupational and recreational noise) are associated with hearing loss. Educating and advising individuals to maintain good general health and fitness would have benefits for hearing preservation 26. Furthermore, we found evidence that among several common chronic diseases, hypertension is the most closely related to hearing loss, which requires special attention to the hearing of patients with hypertension.…”
Section: Discussionmentioning
confidence: 74%
“…Because cardiovascular diseases are influenced by air pollution, air pollution might have an impact on SSNHL 16 . Furthermore, a number of recent studies demonstrated an association between hearing loss and air pollutants from cigarette smoking 17,18 . Current smokers had 1.15 times higher odds of developing hearing loss than nonsmokers (95% confidence intervals [95% CI = 1.09–1.21]) 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Lalwani AK et al gave an interesting observation that hearing loss in adults may commence at an early age and also effects those who are exposed passively to smoking [35]. Age related hearing loss can be attributed to multiple factors like hypoxia, atherosclerosis, oxidative stress, dysfunction of mitochondrion and programmed suicidal death of inner ear cell [36].…”
Section: Original Research Articlementioning
confidence: 99%